GIS based modeling of socio-environmental impacts due to a highway development project- A case study - Agrawal, M L; Agrawal, Anita; Agrawal, Pooja (Recent Research in Science and Technology, 2014)
Infrastructure development is the basic need for economic development of a country. Highway is an important infrastructure for movement of goods and passenger traffic. In the recent years, the need for developing adequate road transportation infrastructure has been realized by Government of India and various state Governments. Major road development projects have been formulated at national level in India. Analysis of socio-environmental impact is an essential component of environmental impact assessment (EIA) that is required for the planning of all major road projects. Most of the socio-environmental attributes are spatial in nature and for a rational assessment of these impacts it is necessary to quantify the impacts considering their spatial variations.In this paper a methodology is demonstrated with reference to a case study of highway development project in India, for the quantification of impact on individual socio-environmental attributes based on the perception of public in the influence area of the project, and the spatial variation of impacts is modeled using Geographic Information System (GIS).